NANOTECHNOLOGIES IN EDUCATION: ALLOTROPIC MODIFICATIONS OF CARBON AS A COMPONENT OF SHUNGITE - M. A. Kosareva; L. A. Baikova; Ye. A. Nikonenko; A. N. Gabdullin (Obrazovanie i Nauka)
The aim of the investigation is to show the possibility of updating of the training program of the discipline «Chemistry» intended for training of engineers of chemical specialties of higher educational institutions on the basis of results of the last researches in the field of nanochemistry. The article is addressed to the scientists and teachers developing the specific fields of science, to students and graduate students who have decided to devote themselves to new perspective science of the 21st century.Methods. The analysis of the works concerning the combinational scattering method (Raman spectroscopy) is made. Exposure to the combinational scattering method and the method of infrared spectroscopy is necessary for the undergraduates who are engaged in synthesis of new nanomaterials on the basis of carbon while deciding of the obtained experimental data. The physical and chemical analysis was used in the research to study the properties and structure of shungite of the Zazhoginsky field – the unique natural mineral containing nanoparticles and the effective sorbent applied to purification of drinking water (emission spectral analysis with inductively coupled plasma, Raman spectroscopy and Infrared spectroscopy).Results and scientific novelty. When processing shungite with toluene, ochroleucous resinous substance was educed; this is an organic substance according to data of IR-spectroscopy. On the basis of the analysis of data of Ramanspectroscopy, the line about 2700 cm–1 is offered to consider as the indicator of crystallinity. A variety of physical and chemical and structural properties in connection on the basis of shungite allows us to speak about chemistry of fullerenes and nanochemistry as the new perspective direction of chemistry.Practical significance. Described data on Raman-spectroscopy will help undergraduates, young scientists and researchers to identify various modifications of carbon in the nanomaterials synthesized by them on the basis of carbon. The data received during the research can be used for laboratory work «Determination of shungit nanocomponents through modern physical and chemical methods», having included it in the subject «Carbon» of the program of discipline «Chemistry». The materials of the article can also serve as a starting point for creation of a special short-term course on studying of materials of group of carbon in the system of advanced training for employees of the entities who are engaged in shungite processing.